Hieronymus on Hermits - Ioana Costa (Revista de Istorie și Teorie Literară)
Hieronymus wrote three portraits belonging to the hagiographic tradition: Vita Beati Pauli, monachi Thebaei, [Vita Malchi] De monacho captiuo and Vita Hilarionis. The solitude of the three hermits is adorned with moments of intense encounters in human and divine dimensions: different as they are, Paulus, Malchus and Hilarion share a sense of harmoniously living, either among people or in secluded places, in the desert or in the mountains.